Evaluation of the sustainable urban drainage systems in as mall town: Case study Paipa, Boyacá, Colombia - Jiménez Avella, Wilson Alejandro; Pérez Hurtado, Omar Felipe (Ingeniería Solidaria, 2026)
Introduction: The current article evaluates the use of SUDS to manage rainwater within the urban area of the municipality of Paipa, research developed at the Pedagogical and Technological University of Colombia in 2020. Methods: The researchers conducted a literature review about SUDS based on the available information regarding the city’s soils, urbanism, hydrology, and sewage system. In addition, in-situ visits took place throughout the study to identify potential areas for implementation, as well as the analysis of alternatives with different SUDS at a pre-feasibility level, taking into account as the most relevant aspects the technical and economic components, and comparing those alternatives with the sewerage renovation project in a sector of the urban center using the EPA SWMM 5.1 software. Results: The study showed the sewage transition process from a combined system to a separate system and the existence of potential places for the implementation of SUDS, which can bring benefits to the design and functioning of the municipal sewer system. Conclusions: It was found that, in this case, SUDS cannot replace conventional sewage systems; however, they can be considered a complement to achieve more integral rainwater management and control. Originality: The study provides a comprehensive perspective on the viability and potential benefits of SUDS implementation in the local context, contributing to a growing body of literature. Limitation: The economic analysis estimated an increase in the total cost of the project. Future research could address these limitations through a broader scope and more detailed financial considerations.